(untitled) (Itinera, 2013)
Shadows and reflections, which often mistakenly appear in the photographs, as superimposition – that technique consisting in impressing many times a sensitive surface over and over or in the overlap of two or more negative during development –, may be included within the framework of the transfiguration process of the error and the rediscovery of the artistic and expressive potential of the photographic medium that strongly concerned the 1920’s avant-garde.